Light Intensity and Temperature Effect on Salvia yangii (B. T. Drew) Metabolic Profile in vitro - Kozłowska, Weronika; Matkowski, Adam; Zielińska, Sylwia (Frontiers in Plant Science, 2022)
Plant in vitro cultures is a feasible system for the testing influence of an environmental factor on the accumulation and chemodiversity of specialized metabolites, especially in medicinal plants. Light and temperature are among the most important factors affecting physiology of plant organism but their influence on specific metabolic pathways is not completely understood. Here, we examined the morphogenetic response, photosynthetic pigments content, lipid peroxidation level, DPPH radical scavenging activity and the production of volatile and non-volatile constituents in Salvia yangii B.T.Drew (syn. Perovskia atriplicifolia Benth.) in vitro cultures kept under different light intensities (70, 130, and 220 µmol m-2 s-1) and two selected temperatures (25 and 30°C). The experiment was continued for 7 months to monitor the changes of the treatment response in time. Phytochemical analysis was performed using chromatographic (GC-MS and UHLPC) and spectrophotometric techniques. Light intensity significantly influenced metabolic response in non-linear manner, whereas temperature-induced adaptive modifications varied within the long cultivation. Significant differences were noted in the content of carnosic and rosmarinic acid, as well as in several sesquiterpenes (alloaromadendrene, β-caryophyllene, α-humulene). At elevated (30℃) temperature, a trend of differently modulated content of two major antioxidants – rosmarinic acid (RA, a phenylpropanoid pathway derived phenolic acid) and carnosic acid (CA, an abietane diterpenoid) was observed, where RA, but not CA, was depending on the light intensity. At 25℃, both compounds depended on light but in various ways. Among the volatile terpenoid compounds, the influence of light was pronounced, leading to modulation of proportions between individual mono- and sesquiterpenes as well as between hydrocarbon and oxygenated compounds. The study provided new information on the metabolic profile plasticity in S. yangii and add to the existing knowledge on the chemical adaptations in plant species from severe habitats.